Immunological analysis in paediatric HIV patients at different stages of the disease - Lian, Yun-Chia; Della-Negra, M.; Rutz, R.; Ferriani, V.; de Moraes Vasconcelos, D.; da Silva Duarte, A.J.; Kirschfink, Michael; Grumach, A.S. (Scandinavian journal of immunology, 2004)
There are only few clinical studies on complement in well-defined (or characterized) paediatric HIV patients. Aim of this study was to evaluate the complement system and immunoglobulins in HIV-infected children and to correlate data to stage of disease. Blood samples of 127 HIV-infected children (11-134 months; 62 male : 65 female) were collected in order to evaluate humoral immunity. The patients were classified according to CDC clinical (N-asymptomatic; A-mild symptoms such as common recurrent infections; B-moderate symptoms such as Candidiasis and herpes infections, meningitis, sepsis and anaemia; C-severe symptoms such as opportunistic infections and neoplasia) and with respect to immunological criteria (T CD4(+) cell count). Analysis of complement system included the classical (CH50), alternative (APH50) pathway activities and plasma concentrations of mannan-binding lectin (MBL), of the C4 allotypic variants C4A and C4B. (ELISA), and of the C3 split product C3d (rocket immunoeletrophoresis). Immunodiagnosis also included CD4(+) and CD8(+) lymphocyte count and immunoglobulin concentrations. Complement activation and consumption was observed in all patients correlating with disease activity. Activated classical and alternative pathways and elevated C3d were significantly correlated with immunologic category 3. C3d levels were also significantly correlated with immunologic category 1. Undetectable CH50 and APH50 were found in two (group C) and 10 patients (n = 2, A = 2, B = 2, C = 4), respectively. Low MBL values were found in 13/127 but without correlation to disease severity. Undetectable C4B levels were observed in three patients, favouring the diagnosis of a complete deficiency. Although not related to clinical symptomatology, a strong ongoing complement activation can be observed in all stages of HIV infection. In contrast to earlier reports MBL could not be considered as a risk factor for HIV.
First published: 03 December 2004
Gesehen am 15.02.2021